Effect of microwave crystallization on the wear resistance of reinforced glass-ceramics - de Carvalho, Ana Beatriz Gomes [UNESP] (2020)
This study compared the wear resistance of different reinforced glass-ceramics crystalized by conventional or microwave firing. The wear rate of three ceramics [one lithium disilicate ceramic (LD): IPS e.max CAD – Ivoclar Vivadent; and two zirconia reinforced lithium silicates: Suprinity – VITA Zahnfabrik (ZLS1) and Celtra Duo – Dentsply (ZLS2)] crystallized by conventional (c) or microwave (mw) firing protocols were collected according to the contact- [two-body (n = 20/gr)] and contact-free wear tests [three-body (n = 20/gr)]. After wear tests performed on ACTA wear machine, mean surface roughness (Ra) and Scanning Electron Microscopy (SEM) analyzes were performed to evaluate the surface alterations. The wear and roughness data (in μm) were evaluated using two-way ANOVA and Tukey post-hoc test (α = 0.05). Two-body wear test revealed that ZLS1 (1.30 ± 1.79)A showed higher wear rate than LD (0.79 ± 2.15)B and ZLS2 (0.85 ± 0.94)B, regardless the crystallization approach. For three-body test, conventional crystallization (0.62 ± 0.4)A showed higher wear rates than microwave (0.22 ± 0.71)B; while the type of ceramic was not significant. The crystallization protocol (p < 0.001) and ceramic material (p = 0.001) affected the surface roughness in the three-body; whereas the two-body test, only the crystallization protocol (p = 0.046). SEM analysis showed a similar and smother surface morphology for LD and ZLS2 compared to ZLS1. Conventional crystallization showed materials more prone to wear than the microwave, in the presence of food bolus. Therefore, the microwave crystallization can be suggested as an alternative to improve the evaluated glass-ceramics wear resistance.